Profile of Patients with Bile Duct Injury in RSUD Dr. Soetomo Period January 224-December 2024 - Santi Santi; Edwin Danardono; Marjono Dwi Wibowo (Journal of World Science, 2025)
Surgical procedures involving the biliary system are among the most common in digestive surgery. Advances in laparoscopic techniques have increased the frequency of bile duct injuries (BDI), a major contributor to morbidity and mortality, remarkably when unrecognized during surgery, which occurs in 25% to 32.4% of cases. This study describes the characteristics of BDI patients treated at RSUD Dr. Soetomo Surabaya from January to December 2024. Employing an observational analytical design with a cross-sectional approach, data were collected from the medical records of 26 patients meeting inclusion and exclusion criteria. Patients who underwent laparoscopic surgery had a shorter average Length of Stay (LOS) of 12.91 days compared to 23.57 days for those with open surgery. Mortality was observed exclusively among patients with a history of open surgery, notably in BDI type E4 cases. These findings highlight the importance of timely recognition and effective management of BDIs to mitigate their significant impact on patient outcomes.